Pengaruh Model Problem Based Learning (PBL) terhadap Kemampuan Memecahkan Masalah dan Hasil Belajar Kognitif Biologi Siswa Kelas VIII - Nihla Utami; Herdiyana Fitriani; Ismail Efendi (Bioscientist : Jurnal Ilmiah Biologi, 2023)
Students' difficulty in understanding the learning material becomes a problem in achieving learning success. This is due to the lack of variety of learning models used by teachers, so far teachers have applied more cooperative learning models. Therefore, researchers try to apply the PBL (Problem Based Learning) learning model, which is one of the learning models that can stimulate students to think in problem-oriented situations. The purpose of this study was to determine the influence of the PBL model on students' problem-solving ability and cognitive learning outcomes. This research was conducted on grade 8th students of SMP Negeri 2 Kediri. This type of research is a pseudo-experiment (quasi-experimental). Data analysis using an independent sample t-test. The population in this study were all students from class 7th to class 9th. While the sample is students in grade 8th A as the experimental class and 8th B as the control class.The samples in this study were students of class 8th A as an experimental class and 8thB as a control class. The sampling technique uses purposive sampling technique. The results of the hypothesis test of problem-solving ability of experimental class and control class students obtained data that the sig < α was 0.009 < 0.05 at a significance rate of 5% so that H 0was rejected and H1 was accepted. In addition, on the results of the cognitive learning hypothesis test of experimental class and control class students, data were obtained that the sig < α was 0.003 < 0.05 at a significance rate of 5% so that H 0 was rejected and H1 was accepted. This shows that the PBL learning model affects students' problem-solving ability and cognitive learning outcomes.